Cancer-related fatigue: Patients' experiences of an intervention at a green care rehabilitation farm. (November 2019) - Johannessen, Berit; Syvertsen, Siri; Kersten, Christian; Berntsen, Sveinung
Highlights: Patients with Cancer Related Fatigue (CRF) experienced the green care farm intervention as helpful for their coping with CRF. CRF patients emphasized how the surroundings, activities, and relations with others were all part of a whole. CRF patients described the activities as 'energy boosting' and 'meaningful'. The stay on the farm had given CRF patients hope for the future. There is a lack of knowledge and competence in the use of Green Care in rehabilitation of patients with CRF.